1997
DOI: 10.1037/0033-2909.122.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Outcome, attrition, and family–couples treatment for drug abuse: A meta-analysis and review of the controlled, comparative studies.

Abstract: This review synthesizes drug abuse outcome studies that included a family-couples therapy treatment condition. The meta-analytic evidence, across 1,571 cases involving an estimated 3,500 patients and family members, favors family therapy over (a) individual counseling or therapy, (b) peer group therapy, and (c) family psychoeducation. Family therapy is as effective for adults as for adolescents and appears to be a cost-effective adjunct to methadone maintenance. Because family therapy frequently had higher tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
336
3
25

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(373 citation statements)
references
References 128 publications
9
336
3
25
Order By: Relevance
“…Metaanalyses of psychotherapy studies that exclude those purely with substance abuse have found average dropout rates of about 50% across the treatment outcome literature (Wierzbicki & Pekarik, 1993). These rates are known to be higher for heroin addicts in particular (Stanton, 1997), and especially in the context of individual therapy (Stanton & Shadish, 1997). Considering all of these factors, we cannot yet say if the attrition in the ACT or ITSF conditions was large because it is not yet clear which benchmark to use.…”
Section: Discussionmentioning
confidence: 89%
“…Metaanalyses of psychotherapy studies that exclude those purely with substance abuse have found average dropout rates of about 50% across the treatment outcome literature (Wierzbicki & Pekarik, 1993). These rates are known to be higher for heroin addicts in particular (Stanton, 1997), and especially in the context of individual therapy (Stanton & Shadish, 1997). Considering all of these factors, we cannot yet say if the attrition in the ACT or ITSF conditions was large because it is not yet clear which benchmark to use.…”
Section: Discussionmentioning
confidence: 89%
“…This estimate, based on eight data sets with over 2,000 total participants, is noticeably smaller than the AMI-assisted reduction of drinking by approximately 20 standard drinks per week reported herein. Additionally, Stanton and Shadish (1997) calculated a combined effect size of 0.38 for family therapy of drug addiction, which is in the same range as the AMI effect sizes in this review. Unfortunately, no good summary estimates exist at this time for the combined effect size of alcohol treatments, chiefly because of the paucity and poor quality of meta-analyses in this area (Wilson, 2000).…”
Section: Benchmarks For Comparisonmentioning
confidence: 90%
“…For each combined effect size, 95% confidence intervals were derived from the variance of d c (Hedges & Olkin, 1985, p. 113 To examine whether the efficacy of AMI interventions was sustained over time, we conducted the most rigorous test possible by examining only those studies that generated effect sizes at both posttreatment and at least one other follow-up period. In this way, the difference between posttreatment and follow-up results is not confounded with any other study features (Stanton & Shadish, 1997). For this subset of studies, Gleser and Olkin's (1994) procedure for stochastically dependent data was used.…”
Section: What Is the Comparative Efficacy Of Amis?mentioning
confidence: 99%
“…Methodological quality. The evidence relating methodological quality and effect size is mixed (e.g., Glass, McGaw, & Smith, 1981;Stanton & Shadish, 1997). We expanded the methodological quality scale developed by Miller et al (1995).…”
Section: Analysesmentioning
confidence: 99%